Important attributes of customer satisfaction in telecom industry: a survey based study - Khan, Nusratullah; Shah, Asadullah; Akram, Muhammad Usman; Ahmad Khan, Shoab (IEEE, 2017)
Customer satisfaction has been acknowledged as critical success factors in any organizations. Recent developments in telecom sector shows that communication services providers (CSPs) are engaged in various marketing and survey activities to discover the satisfaction level of their customers. In general, some subscribers complain about the poor network coverage, voice call quality, internet service etc. while other are satisfied with the quality of services. The aim of this paper is to conduct a servery based study to identify and highlight major attributes that effect customer's satisfaction which will eventually help telecom services providers to improve their customer experience management index. Consequently, this paper examines the factors that have resilient or fragile influence on customer satisfaction. Based on the contemporary research six attributes i.e. network coverage, voice call quality, drop call rate, SMS delivery, internet service and call setup duration have been considered and tested in this research to find the customer satisfaction. For this purpose of study, 200 respondents of a CSP are selected from Islamabad, Pakistan. A telephonic survey is conducted to rate each of the factor and their overall satisfaction. The results reveal that network coverage, voice call quality and internet service have the highest impact on the level of customer satisfaction.